Interação entre genótipos de quinoa e Pratylenchus brachyurus - Schons, Bruna Caroline (2024)
Quinoa is a plant very rich in nutrients for both human consumption and animal feed formulation, making it a viable option for crop rotation. There have not been many studies on the interaction between quinoa and pathogens. With this in mind, the aim of this work was to characterize the resistance of quinoa genotypes to the nematode Pratylenchus brachyurus, verify the plant defence mechanisms involved and determine the ideal amount of inoculum for future studies with this pathosystem. To this end, an experiment was carried out in a greenhouse with 10 quinoa genotypes, which were inoculated with P. brachyurus at 30 days after germination. The variables analyzed 45 days after inoculation were: total number of nematodes per pot, nematodes per gram of root and reproduction factor. 7 of the 10 genotypes tested showed resistance, 2 showed a low degree of susceptibility and one proved to be highly susceptible. One resistant genotype, one with a low degree of susceptibility and one with a high degree of susceptibility were selected for the next experiment, in order to check their behavior at different population levels and define the ideal inoculum level for this pathosystem. The initial populations tested were 250, 500, 1,000, 2,000 and 4,000 nematodes per pot. The genotypes showed that the point of maximum initial population was between 1,000 and 2,000 nematodes per pot. For the analysis of enzymes related to plant defense, the same three genotypes from the previous experiment were used in a new experiment, where root samples were taken in triplicate at 0, 36, 72, 120 and 172 hours after inoculation. The activity of the enzymes polyphenol oxidase (PFO), phenylalanine ammonia lyase (FAL) and peroxidase (POX) was measured, and the total protein content was determined. There was no PFO activity in any of the genotypes. The resistance of genotype 1808 can be explained by the peaks in FAL activity. The low susceptibility of genotype 1303 was well exposed due to its high activity in the enzymes FAL and POX, but some other factor meant that this genotype was not completely resistant. The high susceptibility of the Guará genotype, on the other hand, is a little more complex to understand and requires more in-depth studies.